The economic consequences of changes in the functioning of open pension funds - Jacek Rodzinka; Aleksandra Wojnarowska-Dygdoń; Karolina Palim\~naka (e-Finanse: Financial Internet Quarterly, 2014)
The size of the public debt is now one of the main areas of interest of the entire society. As the size of the debt increases with time, one should consider possible ways of reducing it. Decision makers focus both on ways to reduce the increase in public debt and on ways to reduce its size. State expenditure connected with retirement pensions for citizens is one of the most important expenditure problems in the public sector. Retirement security of citizens is the constitutional duty of the state whereas the security of pension systems and protection of the insured are the most important tasks of the government. Thus, one of the most important factors determining the condition of public finances is the efficiency of solutions in the area of pension funds. This article presents the economic consequences of changes in the functioning of pension funds. It was based on the literature and available data on the website of the Ministry of Finance and the website of the Polish Social Insurance Institution.
Keywords: E60; 330; polish pension system; public debt; pension reform